Friday

August 22, 2014

August 22, 2014

Posted by **Stewart** on Tuesday, June 5, 2012 at 6:58pm.

- Equation of the Tangent Line -
**Reiny**, Tuesday, June 5, 2012 at 8:02pmxy = (xy - x)^(1/2)

x dy/dx + y = (1/2)(xy - x)^(-1/2) (xdy/dx + y - 1)

so at (1,2)

dy/dx + 2 = (1/2)(2 - 1)^(-1/2) (dy/dx + 2 - 1)

times 2

2dy/dx + 4 = (1)(dy/dx + 1)

dy/dx = 1-4 = -3

so tangent is y = -3x + b

with (1,2) lying on it

2 = -3+b

b=5

tangent equation:

y = -3x + 5

check my arithmetic

**Related Questions**

Calculus - If F(x)=x^3−7x+5, use the limit definition of the derivative to...

calculus - Consider the curve defined by 2y^3+6X^2(y)- 12x^2 +6y=1 . a. Show ...

Help Calc.! - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy)/(x^2+y^2+1...

please help; calc - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy)/(x^2+...

Calculus. I need help! - HARDER PARTS WAS 3(x^2+y^2)^2=26(y^2+y^2) Find the ...

COLLEGE CALCULUS. - Use implicit differentiation to find the equation of the ...

math calculus - Use implicit differentiation to find the equation of the tangent...

calculus - -find the equation of the tangent line to the curve y=5xcosx at the ...

math - Find the equation of the tangent line to the curve y=5xcosx at the point...

Calculus - Find the equation of the tangent line to the curve y=2sinx at the ...